Faktor - Faktor yang Berpengaruh Terhadap Densitas Larva Nyamuk Aedes aegypti di Kota Pekalongan - Nila Oktaviani (Universitas Pekalongan, 2010)
Background: Pekalongan regency is one of dengue endemic areas with geographical temperature conditions ranges between 23-350C. Larvae of A. aegypti avaible to live in the temperature between 32 - 340C on the air and 25 -300 C water temperature. This study aimed to know the environmental factors are its main factor to the density of larvae stage of A. aegypti in Pekalongan regency.Method: Research methods was used survey conducted in stratified random sampling technique. Four districts with a total of 10 villages were divided into 3 classes. Endemic classes village chosen 3 member of villages, 4 villages of saprodis classes and 3 classes of potential wards. Each village drawned randomly by 10 houses and set of the sampling point.Result: The results of the multivariate variance analysis showed Based on the results, can be concluded that the most influence key factors to the density are larvae stage of A. aegypti is the temperature and humidity respectively contributed 59.2% and 58.5%. Based on the conclusions, to avoid puddle from high precipitation that could raise the humidity and influencing the temperature is a strategy to reduce the density of each stage of the mosquito A. aegypti.Keyword : Density larvae, Aedes aegypti